Particulate matter-induced metabolic recoding of epigenetics in macrophages drives pathogenesis of chronic obstructive pulmonary disease - Noh, Myungkyung; Sim, Jeong Yeon; Kim, Jisung; Ahn, Jee Hwan; Min, Hye Young; Lee, Jong Uk; Park, Jong Sook; Jeong, Ji Yun; Lee, Jae Young; Lee, Shin Yup; Lee, Hyo Jong; Park, Choon Sik; et al. (Journal of Hazardous Materials, 2024)
Chronic obstructive pulmonary disease (COPD) is a group of illnesses associated with unresolved inflammation in response to toxic environmental stimuli. Persistent exposure to PM is a major risk factor for COPD, but the underlying mechanism remains unclear. Using our established mouse model of PM-induced COPD, we find that repeated PM exposure provokes macrophage-centered chronic inflammation and COPD development. Mechanistically, chronic PM exposure induces transcriptional downregulation of HAAO, KMO, KYNU, and QPRT in macrophages, which are the enzymes of de novo NAD+ synthesis pathway (kynurenine pathway; KP), via elevated chromatin binding of the CCCTC-binding factor (CTCF) near the transcriptional regulatory regions of the enzymes. Subsequent reduction of NAD+ and SIRT1 function increases histone acetylation, resulting in elevated expression of pro-inflammatory genes in PM-exposed macrophages. Activation of SIRT1 by nutraceutical resveratrol mitigated PM-induced chronic inflammation and COPD development. In agreement, increased levels of histone acetylation and decreased expression of KP enzymes were observed in pulmonary macrophages of COPD patients. We newly provide an evidence that dysregulated NAD+ metabolism and consecutive SIRT1 deficiency significantly contribute to the pathological activation of macrophages during PM-mediated COPD pathogenesis. Additionally, targeting PM-induced intertwined metabolic and epigenetic reprogramming in macrophages is an effective strategy for COPD treatment.
Keywords: Chronic inflammation; Chronic obstructive pulmonary disease; Disease development; Epigenetics; Histone acetylation; NAD +; NAD+ metabolism; Particulate Matter; Recoding; SIRT activity; Animals; Epigenesis, Genetic; Histones; Humans; Inflammation; Macrophages; Mice; NAD; Particulate Matter; Pulmonary Disease, Chronic Obstructive; Sirtuin 1; Chronic inflammation; COPD; Histone acetylation; Macrophage; NAD+ metabolism; Particulate matter; SIRT activity